Effectivity of Amount and Form of Herbs Combination as Feed Addition on Broilerâs Performance - Marwandan, Zulfaidha; Agustina, Laily; Mujnisa, Andi (Buletin Nutrisi dan Makanan Ternak, 2013)
The purpose of this research to make effective use of herbs, both powder and liquid, that contains the same bioactive substances to improve the performance of broilers. The research conducted in March through May 2012 at the Laboratory of Omnivore, Faculty of Animal Sciense, Hasanuddin University. The material used 100 birds DOC (unsexed), molasses, EM4, water, 12 herbs, 7 herbs, and basic feed. The design used completely randomized design (CRD) consisting of 4 treatments and 5 replications (each unit consisting of five experimental chickens). The treatment consists of the use of herbs A1 (a combination of 12 liquid herbs ingredients), A2 (a combination of 7 liquid herbs ingredients), A3 (a combination of 12 herbs powder ingredients), and A4 (a combination of 7 herbs powder ingredients). Parameters measured broiler performance including weight gain, feed intake, and feed conversion. The results of analysis of variance showed that the average body weight gain, feed intake and feed conversion had no significant effect (P> 0.05) on the provision of a combination of herbal ingredients in powder and liquid form, but uses 7 ingredients of herbal powders tend to do better in improving feed conversion in broilers. The conclusion of this research is the provision of combination of herbs amount liquid and powder form had no effect on weight gain, feed intake, and feed conversion of broilers. 7 herbs ingredients have the best effect in terms of efficient to use.